Drug-drug interaction-related uncontrolled glycemia - Hammad, Mohamed Anwar; Tangiisuran, Balamurugan; Kharshid, Abeer Mohamed; Abdul-Aziz, Noorizan; Hassan, Yahaya; Aziz, Nor Azizah; Elsayed, Tarek Mohamed Ali (Medknow Publications, 2017)
Context: The literature of drug-drug interaction (DDI)-related uncontrolled causality, and preventability of DDI-induced UCG (HbA1c >7%) in outpatients glycemia (UCG) among outpatients with Type 2 diabetes mellitus is still limited. Aims: The aim of this study is to identify the prevalence, mechanism, severity, with Type 2 diabetes. Settings and Design: A cross-sectional study was conducted in Penang General Hospital. Methods: A computerized system for DDI checking was used to assess the severity and mechanism of DDIs. Drug interaction probability scale was used to evaluate the likelihood of DDIs. Preventability of DDIs has been determined by the instrument of Hallas. The UCG prevalence related to DDIs was further assessed. Statistical Analysis Used: SPSS 21.00 was used in this study. Results: From 425 outpatients with HbA1c% test, their mean age was 58.7 ± 12.8 years. Only 225 (52.9%) cases had controlled glycemia while 200 (47.1%) cases with UCG. They had multiple comorbidities, with a mean number of 3.8 ± 2.2/patient and often prescribed with multiple medications, with a mean number of 6.33 ± 4.67/patient. It has been detected that 86 DDIs causing UCG in 46 patients (23%) with range of (1-4) DDIs per patient. Drugs with DDI-induced UCG were as follows: diuretics (79%), salbutamol (9.2%), cortisones (5.8%), and others (6%). The majority of these DDIs were categorized as possible (77.9%) and preventable (37%). Conclusion: Nearly one-quarter of UCG was induced by DDIs; most of these DDIs are possible, and more than one-third are preventable. It was concluded that thiazide diuretics have the highest prevalence of DDI-related UCG.